The Implementation of the Transition of Manual Land Registration Services to Electronic - Guntara, Ricky (Jurnal Konstatering, 2022)
This study aims to analyze: 1) Implementation of the transition from manual to electronic land registration services in Cirebon Regency. 2) Constraints and solutions in implementing the transition from manual to electronic land registration services in Cirebon Regency. The approach method used in this research is a sociological juridical approach. The research specification used is descriptive analytical research. This type of data uses primary data and secondary data with library research and interview collection methods. The data analysis method used in this research is qualitative analysis. The results of the study concluded: 1). The implementation of the transition from manual to electronic land registration services in Cirebon Regency can provide many benefits for the community including minimizing fraud, minimizing land brokers/mafia, preventing corruption, preventing double certificates, saving costs, preventing disputes, conflicts and land cases, minimizing physical meetings, and reducing the intervention of unauthorized parties. The implementation of land services electronically can be done through the Touch Tanahku application. The result of the implementation of electronic land registration is an electronic certificate. Electronic certificates are legally used as evidence and can provide legal certainty because they are guaranteed by laws and regulations. 2). Obstacles in the implementation of the transition from manual to electronic land registration services in Cirebon Regency are the lack of public understanding of electronic certificates, lack of completeness of files, unprepared human resources for implementation, uneven internet network, and uneven land mapping.Keywords: Certificate; Electronic; Land; Registration.